Neuromodulation Leads to a Burst-Tonic Switch in a Subset of VIP Neurons in Mouse Primary Somatosensory (Barrel) Cortex. (18th June 2019) - Prönneke, Alvar; Witte, Mirko; Möck, Martin; Staiger, Jochen F
Abstract: Neocortical GABAergic interneurons expressing vasoactive intestinal polypeptide (VIP) contribute to sensory processing, sensorimotor integration, and behavioral control. In contrast to other major subpopulations of GABAergic interneurons, VIP neurons show a remarkable diversity. Studying morphological and electrophysiological properties of VIP cells, we found a peculiar group of neurons in layer II/III of mouse primary somatosensory (barrel) cortex, which showed a highly dynamic burst firing behavior at resting membrane potential that switched to tonic mode at depolarized membrane potentials. Furthermore, we demonstrate that burst firing depends on T-type calcium channels. The burst-tonic switch could be induced by acetylcholine (ACh) and serotonin. ACh mediated a depolarization via nicotinic receptors whereas serotonin evoked a biphasic depolarization via ionotropic and metabotropic receptors in 48% of the population and a purely monophasic depolarization via metabotropic receptors in the remaining cells. These data disclose an electrophysiologically defined subpopulation of VIP neurons that via neuromodulator-induced changes in firing behavior is likely to regulate the state of cortical circuits in a profound manner.